Triangulating the World Trade Organization - Charnovitz, Steve (2002)
Presents an analytical method for considering proposals to expand the scope of the WTO. Shows why the purpose of the WTO is not self-evident and how a framework can be useful for improving the debate about the organization's mission. Presents a three-category framework reflecting the different ambits in which the WTO operates. Explains how the frames can help triangulate the WTO within international law.